2016
DOI: 10.1016/j.biocon.2016.05.031
|View full text |Cite
|
Sign up to set email alerts
|

Modest recovery of biodiversity in a western European country: The Living Planet Index for the Netherlands

Abstract: a b s t r a c tWe calculated a Living Planet Index (LPI) for the Netherlands, based on 361 animal species from seven taxonomic groups occurring in terrestrial and freshwater habitats. Our assessment is basically similar to the global LPI, but the latter includes vertebrate species and trends in population abundance only. To achieve inferences on trends in biodiversity more generally, we added two insect groups (butterflies and dragonflies) and added occupancy trends for species for which we had no abundance tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 27 publications
4
45
1
Order By: Relevance
“…These authors noted that their results for the most recent decades contradict Carvalheiro et al (), as extinctions might be increasing again. Van Strien et al () observed a modest recovery of biodiversity in the Netherlands, measured as the living planet index, from 1990 to 2014. It is concentrated, however, in the freshwater habitats and with diversity decreases in the habitats where wild bees typically occur.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These authors noted that their results for the most recent decades contradict Carvalheiro et al (), as extinctions might be increasing again. Van Strien et al () observed a modest recovery of biodiversity in the Netherlands, measured as the living planet index, from 1990 to 2014. It is concentrated, however, in the freshwater habitats and with diversity decreases in the habitats where wild bees typically occur.…”
Section: Discussionmentioning
confidence: 99%
“…Repeated observations within years are required at a fixed set of locations for estimating occupancy, which does not match with the structure of the bee data and the lack of data in some years. van Strien et al () constructed detection/nondetection records per square kilometer cell with observations and analyzed these per species separately. In this dataset, there is no guarantee that collectors sampled in a manner representative of the species locally present and I therefore refrain from such reconstructions.…”
Section: Methodsmentioning
confidence: 99%
“…This procedure is widely adopted to create indicators for biodiversity change (e.g. global LPI, Loh et al., ; Van Strien et al., ). The geometric mean is stable when positive and negative trends, as well as their magnitude, are in balance.…”
Section: Methodsmentioning
confidence: 99%
“…We included the uncertainty due to sampling error of species indices into the confidence limits of our indicator, thereby ensuring error propagation. Finally, we applied LOESS (locally weighted polynomial regression) to produce smoothed indices and confidence intervals (Van Strien et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…Species abundance on agricultural land has declined in recent decades, although for some species the decline has been stabilised (CBS et al, 2012;Van Strien et al, 2016) (Agrimatie, n.d.). For an analysis of financial results in dairy farming, see Alfa (2010; Brouwer et al, 2016).…”
Section: Source: Cbs (2015)mentioning
confidence: 99%